Single Stem Cultivation and Performance of Cucumber Cultivars During Winter-Spring Seasons - Subedi, PP; Sharma, MD (Journal of the Institute of Agriculture and Animal Science, 2005)
This experiment was conducted to assess the response of three cucumber cultivars Bhaktapur Local, Japanese Green and Korean White to single stem cultivation in randomized block design with six replications. The experiment was conducted in Yampaphant (450 m asl) during December 2001 to April 2002. The cv. Bhaktapur Local produced significantly higher number of male flowers (32/m2), while the Korean White produced significantly higher number of female flowers (37.5/m2) and a very few number of male flowers. The cv. Korean White produced significantly higher number of marketable fruits (20/m2) and higher marketable yield (48.2 t/ha) followed by Japanese Green (45.7 t/ha). The cv. Bhaktapur Local produced the lowest marketable yield (33.3 t/ha). Hence single stem cultivation performed well in winter-spring season. Key words: Cucumber cultivars, single stem cultivation, late winter-springJ. Inst. Agric. Anim. Sci. 26: 149-151 (2005)